2014
DOI: 10.1080/01635581.2014.936946
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Necrosis in Human Liver Tumor Cells by α-Phellandrene

Abstract: α-Phellandrene (α-PA) is a component of dietary spices and herbs. The effect of α-PA on anticancer is unclear. This study aims to investigate the effects of α-PA on liver tumor cell death fate. Human liver tumor (J5) cells were incubated with α-PA and analyzed for cell cycle distribution, expression of Bax, Bcl-2, poly (ADP-ribose) polymerase (PARP) protein, and caspase-3 activity of J5 cells, and levels of nitric oxide (NO) production, lactate dehydrogenase (LDH) leakage, and ATP depletion were also analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…α-phellandrene also significantly inhibited cell viability of liver tumor cells at a concentration of 30 µM. This inhibition of cell viability was due to necrosis caused by increased nitric oxide, reactive oxygen species production and lactate dehydrogenase leakage, ultimately leading to ATP depletion [282]. A subsequent study by this group found that treatment with α-phellandrene also induced autophagy via downregulation of PI3K-I, mTOR, and Akt and upregulation of phosphorylated Bcl-2, PI3K-III, LC3-II and Beclin-1.…”
Section: Alpha-phellandrenementioning
confidence: 94%
“…α-phellandrene also significantly inhibited cell viability of liver tumor cells at a concentration of 30 µM. This inhibition of cell viability was due to necrosis caused by increased nitric oxide, reactive oxygen species production and lactate dehydrogenase leakage, ultimately leading to ATP depletion [282]. A subsequent study by this group found that treatment with α-phellandrene also induced autophagy via downregulation of PI3K-I, mTOR, and Akt and upregulation of phosphorylated Bcl-2, PI3K-III, LC3-II and Beclin-1.…”
Section: Alpha-phellandrenementioning
confidence: 94%
“…Hsieh LC et al [53] have demonstrated that sub-micromolar concentrations of α-phellandrene promote cell death by autophagy through modulating the expression of mTOR and LC-3II, p53 signaling and NF-KB activation in J5 liver tumor cells. In addition, the toxicity of this compound involves necrosis when tested in liver cancer cell lines [54]. Furthermore, there is a 12-fold higher percentage of the sesquiterpene hydrocarbon E-caryophyllene in F-PSEO than L-PSEO.…”
Section: Discussionmentioning
confidence: 99%
“…rigida (0.1%) [21] Z. clinopodioides subsp. bungeana [201] Z. tenuior (0.48%) [94,179] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] Molecules 2016, 21, 826 14 of 53…”
Section: α-Thujene (34)mentioning
confidence: 99%
“…clinopodioides (2.0%) [184] Inhibition of P-glycoprotein-mediated transport of different substances [213] Suppression of CNS in mice [214,215] Some topical anti-inflammatory activity in carrageenan-induced paw edema in rats [216] Antioxidant activity in various free radical scavenging tests [217,218] Antifungal activity tested against some food spoilage yeasts [219] Larvicidal activity against mosquitoes Aedes aegypti and A. albopictus [206] Antiviral activity against herpes simplex virus type 1 in vitro [220] Review on some effects on cardiovascular system [221] Trypanocidal activity against Trypanosoma evansi [222] Z. tenuior (0.48%) [94,179] α-Phellandrene (35) Z. clinopodioides (0.3%) [184] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] α-Terpinene (36)…”
Section: α-Thujene (34)mentioning
confidence: 99%